The changing pattern and determinants of declining consanguinity in Jordan during 1990-2012 - M. Mazharul Islam (Taylor & Francis Group, 2018)
Background: Consanguinity is a deep rooted cultural trait in Jordan. Aim: To examine the patterns and determinants of declining rates of consanguineous marriage in Jordan during 1990-2012 in the context of the changing pattern of socio-economic and demographic conditions. Materials and methods: The data come from the 1990 and 2012 Jordan Population and Family Health Surveys (JPFHSs). A total of 6461 women in 1990 and 11,352 women in 2012 were successfully interviewed. Descriptive and multivariate statistical techniques were used for data analysis. Results: Consanguinity was found to be widely practiced (35% in 2012) until recent times in Jordan. However, there has been a secular declining trend over the last few decades as the practice of consanguinity has declined from 56% in 1990 to 35% in 2012. Increasing age at marriage and female education, higher level of education of husbands, declining family size, increasing rate of urbanisation and female employment, exposure to mass media and higher economic status appeared as significant predictors of declining consanguinity in Jordan. Conclusions: The findings of this study support Goode's hypothesis of a decrease of consanguinity with modernisation. Although consanguinity is a deeply rooted cultural trend in Jordan, it is gradually losing ground due to modernisation and socio-demographic transition of the country.